Proton Therapy for Primary Bone Malignancy of the Pelvic and Lumbar Region – Data From the Prospective Registries ProReg and KiProReg - Worawongsakul, Rasin; Steinmeier, Theresa; Lin, Yi-Lan; Bauer, Sebastian; Hardes, Jendrik; Hecker-Nolting, Stefanie; Dirksen, Uta; Timmermann, Beate (Frontiers in Oncology, 2022)
Purpose/Objective(s): Multimodality treatments together with local proton therapy (PT) are commonly used in unresectable primary bone malignancies in order to provide better tumor control rate while maintaining good feasibility. The aim of this study is to provide data on outcome of PT for the challenging cohort of pelvic and lumbar bone tumors. Methods and Materials: This retrospective study includes all patients with primary bone malignancy of the pelvis and lumbar spine receiving PT in our institution between May 2013 and December 2019 enrolled in the prospective registries KiProReg and ProReg collecting information on demographics, treatment, tumor characteristics, toxicities and outcome. Results: Eighty-one patients were enrolled with a median age of 19.7 years (1.3-85.8). The median follow-up time was 27.5 months (1.2-83.2). The majority of patients were male (64.2%), ECOG status of 0-1 (75.2%), underwent only biopsy (50.6%), received chemotherapy (69.1%) and was assigned for definite PT (70.4%). The predominant tumor characteristics were as follows: Ewing’s sarcoma histology (58%), negative nodal involvement (97.5%) and no metastasis at diagnosis (81.5%). Median maximal diameter of tumor was 8 cm (1.4-20).LC, EFS and OS rate were 76.5%, 60% and 88.1% at two years and 72.9%, 45.7% and 68.9% at three years, respectively. Age over 20 years was a significant negative factor for LC, EFS and OS. Metastatic disease at initial diagnosis affected OS and ECOG status of 2-4 affected EFS only. Regarding 17 relapsed cases (21%), isolated distant relapse was the most common failure (46.9%) followed by local failure (40.6%). Eleven out of 14 evaluable patients relapsed within high-dose region of radiotherapy. Acute grade 3-4 toxicity was found in 41 patients (50.6%) and all toxicities were manageable. Late grade 3 toxicity was reported in 7 patients (10.4%) without any of grade 4. Most common higher grade acute and late side effects concerned hematologic and musculoskeletal toxicity. Conclusion: Proton therapy resulted in good oncological outcomes when being part of the multimodality treatment for pelvic and lumbar primary bone malignancies. However, distant metastases and local failures within the high-dose region of radiotherapy are still a common issue. Acute and late toxicities of combined therapy were acceptable.